622 Exploring the impact of community-level trauma and implications for injury prevention. (1st September 2016) - Davis, Rachel; Pinderhughes, Howard
Abstract : Background: Communities that experience high rates of violence typically experience high levels of trauma. Trauma not only has a significant impact on development, health, and well-being, but can also be a barrier to the successful implementation of injury prevention strategies. The predominant construct for addressing trauma is currently based in a medical model at the individual level. In high-violence neighbourhoods, however, trauma can manifest at the community-level. To address this scale of trauma means not only insisting on trauma-informed care for individuals, but also exploring how to address trauma at the population level. Objective: This session presents an emerging construct for population-level trauma and poses a framework to inform the development and implementation of strategies to prevent injury and trauma and promote community healing. Results: With funding from Kaiser Permanente, Prevention Institute and Dr. Howard Pinderhughes conducted a study to explore trauma at the population level, how it impacts other community health improvement efforts, and emerging strategies. The impact of trauma extends beyond the individuals who directly witness or experience violence. Trauma is also produced by structural violence, which prevents people and communities from meeting their basic needs. The result is both high levels of trauma across the population and a breakdown of social networks, social relationships and positive social norms across the community – all of which could otherwise be protective against violence and other health outcomes. The study found that the impact of trauma extends beyond individuals who directly experience violence. This results in both high levels of trauma across the population and a break-down of social networks, social relationships and positive social norms across the community – all of which could otherwise be protective against violence. In order for communities to build resilience, strategies must be implemented that build on indigenous knowledge, expertise, and leadership to yield strategies that are culturally relevant and effective After this session, attendees should be able to discuss various ways community trauma can manifest at the community level. During this session, we will briefly describe the findings of the study and present the emerging framework., along with examples of communities that are developing and implementing community level strategies. Prevention Institute will then facilitate a peer-to-peer discussion exploring how community level trauma shows up in communities, and emerging resilience strategies to prevent and address it. Conclusions: The community trauma framework has implications for practitioners, researchers, and advocates developing strategies to improve safety by overcoming community-level trauma as a barrier to successful injury prevention.